THE LANGUAGE STYLE USED IN PRESENTATION ON YOUTUBE BY ENGLISH LANGUAGE EDUCATION STUDENTS - Dwitamayanti, Ni Kadek; Putra, I Nyoman Adi Jaya; Saputra, I Nyoman Pasek Hadi (Universitas Pendidikan Ganesha, 2021)
People's thoughts on a particular topic were represented through language style. This study aimed at investigating kinds and functions of language style that students use when giving presentations on YouTube. There were a total of 15 students who took part in the study. A descriptive qualitative design was used in this study. The observation sheet and table classification of the types of language styles were used as research instruments. The findings revealed that concrete word (14%), abstract word (32%), general word (4%), specific word (4%), and scientific word (10%) were used in the language style based on diction. Meanwhile, antithesis (10%), repetition (10%), climax (12%), and anticlimax (4%) were among the language style based on sentence structure. Abstract word and climax made prominent appearances in both classifications, according to both data. The functions of the language style were expressive (18%), directive (43%), referential (17%), metalinguistic (7%), and phatic (15%). It suggested that directive had the most prominent expressions.